Effects of dopants on the conductivity of polyaniline Synthesized by chemical oxidation and electrochemical methods - AWUAH, Joseph Asare (KNUST, 2026)
A Thesis submitted to the Department Of Physics, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirement for the degree of MASTER OF PHILOSOPHY (MATERIALS SCIENCE) College of Science